2017
DOI: 10.1194/jlr.p071860
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and fine-mapping of loci associated with MUFAs through trans-ethnic meta-analysis in Chinese and European populations

Abstract: MUFAs are unsaturated FAs with one double bond and are derived from endogenous synthesis and dietary intake. Accumulating evidence has suggested that plasma and erythrocyte MUFA levels are associated with cardiometabolic disorders, including CVD, T2D, and metabolic syndrome (MS). Previous genome-wide association studies (GWASs) have identified seven loci for plasma and erythrocyte palmitoleic and oleic acid levels in populations of European origin. To identify additional MUFA-associated loci and the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Sphingomyelins have previously been shown to be associated with SGPP1 [41], but the associations of sphingomyelins with these other three loci are reported here for the first time. GCKR has been shown to be associated with total cholesterol and triglycerides (see Figure 2), and has also been associated with the plasma phospholipid fraction fatty acids 16:0 and 16:1 [42, 43]; most lipids that we found to be associated with GCKR (Supplementary Figure 6g) are likely to contain these particular fatty acids. It has been suggested that the glucokinase receptor, encoded by GCKR , affects the production of malonyl-CoA, an important substrate for de novo lipogenesis [42].…”
Section: Discussionmentioning
confidence: 82%
“…Sphingomyelins have previously been shown to be associated with SGPP1 [41], but the associations of sphingomyelins with these other three loci are reported here for the first time. GCKR has been shown to be associated with total cholesterol and triglycerides (see Figure 2), and has also been associated with the plasma phospholipid fraction fatty acids 16:0 and 16:1 [42, 43]; most lipids that we found to be associated with GCKR (Supplementary Figure 6g) are likely to contain these particular fatty acids. It has been suggested that the glucokinase receptor, encoded by GCKR , affects the production of malonyl-CoA, an important substrate for de novo lipogenesis [42].…”
Section: Discussionmentioning
confidence: 82%
“…After chromatographic separation, the isolated lipids are ionized that are detected using a mass analyser [ 31 ]. GC–MS provides limited coverage of the lipidome and hence, is restricted to studies focused on specific lipid classes and fatty acids quantifications [ 43 45 ]. In recent times, shotgun lipidomics has gain popularity due to its relative simplicity of operation and short run times to quantify hundreds of lipids [ 32 34 ] and has been applied in several large-scale studies [ 12 , 46 , 47 ].…”
Section: Analytical Methods In Lipidomicsmentioning
confidence: 99%
“…As epidemiological studies have demonstrated that distinct molecular species (e.g., TGs and PCs) have different or opposite effect on disease outcomes, genetic variants/loci could potentially have different effect on functionally diverse lipid species. To ascertain that, several genome-wide association studies have been performed with individual lipid species (Table 3 ) [ 12 , 38 45 , 83 100 ]. These studies have not only identified several new loci/genes contributing to lipid metabolism, but also provided novel mechanistic insights to the known loci identified for traditional lipids.…”
Section: Genetic Regulation Of Lipidomementioning
confidence: 99%
“…57,58 Moreover, a case-control study showed that the adverse effect of the rs3786897 polymorphism of peptidase D (PEPD) on T2D could be alleviated by a higher level of erythrocyte phospholipid n-3 FAs. 59 [60][61][62] Meanwhile, we demonstrated different effect sizes of FADS1 variants on PUFA levels between Chinese and Europeans, and a lower allele frequency of the rs3734398 polymorphism of ELOVL fatty acid elongase 2 (ELOVL2) for Chinese compared with Europeans in a transethnic analysis. 62 These findings suggest potential effects of different genetic backgrounds on PUFA metabolism, and highlight how important it is to establish dietary fat recommendations for the Chinese population based on evidence from Chinese studies.…”
Section: Integration Of Genomic and Metabolomic Datamentioning
confidence: 83%
“…Moreover, a case‐control study showed that the adverse effect of the rs3786897 polymorphism of peptidase D ( PEPD ) on T2D could be alleviated by a higher level of erythrocyte phospholipid n‐3 FAs . Recently, we identified 10 novel genetic loci, namely three for blood saturated FAs (LIM homeobox transcription factor 1 [ LMX1A ], AMP deaminase 3 [ AMPD3 ], ceramide synthase 4 [ CERS4 ]), three for blood monounsaturated FAs (fatty acid desaturase 1/2 [ FADS1/2 ], polycystin 2 like 1, transient receptor potential cation channel [ PKD2L1 ], glucokinase regulator [ GCKR ]) and four for blood PUFAs (MYB proto‐oncogene, transcription factor [ MYB ], 1‐acylglycerol‐3‐phosphate O ‐acyltransferase 4 [ AGPAT4 ], diacylglycerol O ‐acyltransferase 2 [ DGAT2 ], palmitoyl‐protein thioesterase 2 [ PPT2 ]), in our GWAS analysis in cooperation with the Cohorts from Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium . Meanwhile, we demonstrated different effect sizes of FADS1 variants on PUFA levels between Chinese and Europeans, and a lower allele frequency of the rs3734398 polymorphism of ELOVL fatty acid elongase 2 ( ELOVL2 ) for Chinese compared with Europeans in a transethnic analysis .…”
Section: Integration Of Genomic and Metabolomic Datamentioning
confidence: 99%